Brain exercise in elderly: NeuroSky smarter Kit investigation - Chaipakornwong, Tinnaphol; Sittiprapaporn, Phakkharawat (Asian Journal of Medical Sciences, 2020)
Background: The measurement analysis of the brainwaves can show whether or not human’s mental or cognitive status is in a sober state. The speed of the computer signal processing technology increased until it could sufficiently process the complex brainwave signals measured in real-time. Therefore, the information about the mental status thus gradually revealed a research in information science called affective computing. Aims and Objective: The purpose of this study was to study the use of NeuroSky Smarter Kit in brain exercise training program by Brainwave Cloud Classroom (BCC) system, on both attention and meditation levels’ changes in elderly. Materials and Methods: The sample of this study were fifteen participants, which were four men and ten women, aged 61-84 years old. All participants were measured their attention and meditation levels by NeuroSky Smarter Kit prior to the brain training program. During the brain exercise training program by Brainwave Cloud Classroom (BCC) system, should any participant could not proceed to the next session, he/she was measured their attention and meditation levels again. They were allowed to break for fifteen to thirty minutes or as much as they needed. Then, the second brain training was done and that participants were measured their attention and meditation levels again. Results: The result showed that attention and meditation levels were gradually increased with no statistically significant. Both theta and alpha brainwaves were increased statistically significant. Conclusion: The attention level increased while the meditation level was sustained similar to before brain exercise training. Some electroencephalographic activities including theta and alpha brainwaves were gradually increased with statistically significant while gamma brainwave did not change.